Vascular Endothelial Growth Factor Genetic Variant is Associated with In-Stent Restenosis after Percutaneous Coronary Intervention - Saeedeh Asgarbeik; Aida Vahidi; Mandana Hasanzad; Mojgan Asadi; Mahsa M.Amoli (Journal of Tehran University Heart Center, 2022)
Background: In-stent restenosis (ISR) is an inevitable complication of percutaneous coronary intervention, with genetic factors thought to play a role in its pathogenesis. The VEGF gene can have an inhibitory effect on ISR development. Accordingly, in the present study, we investigated the role of −2549 VEGF (insertion/deletion [I/D]) variants in ISR formation.